Schreibberatung: Eine Systematik - Knorr, Dagmar (Schreibwissenschaft, 2024)
What challenges must writing consultants meet when working in an academic context? What characterizes language-sensitive writing consulting? Writing consultants support writers in developing their academic writing skills and mastering the text production process. To do so, they draw on knowledge about academic texts and the writing process described in the "Systematics of Academic Writing." Their actions are also subject to contextual and personal requirements. The "Systematics of Writing Consulting" describes the facets of knowledge required to meet these challenges, contextualizes them in various disciplinary discourses, and brings them together in a writing-scientific perspective.